Acute phase proteins in calves naturally infected with cryptosporidium - Mohammed T. S. Al-Zubaidi (Al-Qadisiyah Journal of Veterinary Medicine Sciences, 2015)
Infectious diarrhea remains one of the most important health challenges in dairy industries during the first four weeks of life, with Cryptosporidium infection as one of the main causes of this diarrhea. This study aimed to evaluate the blood concentration of some acute phase proteins in calves naturally infected with Cryptosporidium. Ninety-six, 1 day to 4 week-old Holstein calves were allotted into a control group (G1 n=48 healthy calves) and calves infected with Cryptosporidium (G2 n=48). Blood and fecal samples were collected from each calf on the same day. Enzyme-Linked Immuno-Sorbent Assay (ELISA) was used to estimate serum levels of haptoglobin (Hp), serum amyloid A (SAA), and tumor necrosis factor alpha (TNFα), while gel electrophoresis was used to determine serum level of fibrinogen. Serum SAA, Hp, and fibrinogen significantly increased in infected calves, whereas there was no significant difference in serum level of TNFα between the two groups.